Influência do material oclusal na distribuição de tensões em próteses implantossuportadas unitárias - Santiago Júnior, Joel Ferreira [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Almeida, Daniel Augusto de Faria [UNESP]; Batista, Victor Eduardo de Souza [UNESP]; Falcón-Antenucci, Rosse Mary [UNESP]; Verri, Fellippo Ramos [UNESP] (My University, 2013)
Objective: the aim of this study was to evaluate the influence of occlusal veneering material in single fixed implant-supported crowns through the 3-D finite element method. Material and methods: Four models were fabricated using the Rhinoceros 4.0, SolidWorks, and InVesalius softwares. Each model represented a block of mandibular bone with an external hexagon implant of 5 mm x 10 mm and different veneering materials including NiCr (1), porcelain (2), composite resin (3), and acrylic resin (4). An axial load of 200 N and an oblique load of 100 N were applied. Results: model (2) with porcelain veneering presented a lower stress concentration for the NiCr framework, followed by the composite resin and acrylic resin. The stress distribution to the implant and bone tissue was similar for all models. Conclusions: there is no difference of stress distribution to the implant and supporting structures by varying the veneering material of a single implant-supported prosthesis.

O objetivo deste estudo foi avaliar a influência do material oclusal em próteses implantossuportadas unitárias, através do método de elementos finitos 3-D. Material e Métodos: quatro modelos foram fabricados utilizando os softwares Rhinoceros 4.0, SolidWorks e InVesalius. Cada modelo representou um bloco de osso mandibular com um implante de hexágono externo de 5 mm x 10 mm e diferentes materiais oclusais, incluindo NiCr (1), porcelana (2), resina composta (3) e resina acrílica (4). Uma força axial de 200 N e uma força oblíqua de 100 N foram aplicadas. Resultados: o modelo (2) com material oclusal de porcelana apresentou menor concentração de tensões para a infraestrutura de NiCr, seguido de resina composta e resina acrílica. A distribuição de tensões para implante e tecido ósseo foi similar para todos os modelos. Conclusão: não há diferença na distribuição de tensões para implante e estruturas suportes, variando-se o material oclusal de próteses implantossuportadas unitárias.
Influence of occlusal material on stress distribution in single implant-supported prostheses
Keywords: Finite element analysis; Dental prosthesis implant-supported; Biomechanics; Dental implants; Análise de elementos finitos; Prótese dentária fixada por implante; Biomecânica; Implantes dentários